Study of prenatal, natal, and neonatal risk factors associated with autism - Sahana, K S; Bhat, Sham S; Kakunje, Anil (Indian Journal of Child Health, 2018)
Introduction: Autism spectrum disorder is one of the common developmental disabilities. Underlying autism etiology is most likely polygenic but environmental factors may also contribute. Obstetrical and neonatal risk factors have been considered for the development of autism. Objectives: The objectives of the study were to know the presence of antenatal, perinatal and neonatal complications in autistic children. Materials and Methods: Children who were diagnosed with autism were included in the study. Visits were made to the special school for the collection of data with prior consent, and birth details were collected from the parents. Results: A total of 54 children were included in the study. Age of the children ranged from 3 years to 17 years with the mean age of 10.93 years. 39 (72.2%) were boys and 15 (27.8 %) were girls. Advanced maternal age at delivery was noted in 24% of the cases. Antenatal risk factors were seen in 24% of cases and natal risk factors in 20% of the cases. 17% had birth asphyxia. Neonatal intensive care unit admission was noted in 20% of cases, neonatal seizures in 5.6%, respiratory distress in 9.3%, and low birth weight in 17% of cases. 60% of them were first born. Overall, the presence of antenatal, natal, and postnatal risk factors were noted in 57% autism cases. Conclusion: In children with autism, there is increased prevalence of obstetric and neonatal risk factors. These variables should be examined in future for precise assessments of exposures.